The Electronic Industry Intra-Industry Trade Analysis in 10 Indonesian Trading Partners : Case Study: Refrigerator Products - Vierke, Intan; Syaiful Ahmar; Achmad Sanusi (Kirana Publisher (KNPub), 2023)
The importance of international trade in the context of refrigerator products makes intra-industry trade intensity (IIT) a very relevant tool. In international trade policymaking, particularly concerning refrigerator products, IIT is essential for understanding global economic dynamics, trade patterns, and trade relations between Indonesia and its trading partners. The use of IIT can provide deep insights into the extent to which there is an exchange of similar or similar but different goods among countries involved in the trade of refrigerator products. Therefore, the focus of the problem in this context is the extent to which the Indonesian refrigerator industry depends on ten trading partners in terms of exports and imports of refrigerator products and how this degree of dependence affects the stability of the sector in the face of changing global trade conditions. Regarding exports, India is the most important trading partner with a significant contribution, indicating a dependency that requires special attention. India has also emerged as an essential supplier, albeit with a lower level of dependence. Diversifying export and import markets should be considered to reduce the risk of dependence on certain trading partners. IIT analysis can also provide insights into the competitiveness of Indonesian products in the international market —improvement of export success also depends on understanding intra-industry trade dynamics.